Distribution of Cd, Cu, Pb and Zn in the Estuary of Sungai Terengganu in Relation to Salinity During the Pre-Monsoon Season - Shaharuddin Mohd Sham (Terengganu: Universiti Putra Malaysia Terengganu, 2014)
Trace metal content of the estuary of Sungai Terengganu has been determined. Two samplings were done, on the 23rd of September and the 1st of October.